(untitled) (Música Hodie, 2016)
Giuseppe Millico, best known in his time as a castrato singer and to posterity for his connections with Christoph Gluck, was also a composer of songs and dramatic works. This article traces the career of one of the latter, the pastoral drama La pietà d’amore. It was first performed in Naples in 1782, where, unusually, it was also published. It subsequently came to be staged in Lisbon, the following year, and at the Ópera Nova Theatre, Rio to Janeiro, probably in 1786. In addition, certain aspects of the preface to the printed edition are considered, as well as manuscript scores and libretti relating to the known productions. Keywords: Giuseppe Millico; La pietà d’amore; Ópera Nova; Ajuda; Antonio Lucchesi.